2022
DOI: 10.1111/iwj.13754
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting skin necrosis risk after open reduction and internal fixation for tibia fractures

Abstract: The purpose of our study was to determine the risk factors for skin necrosis after open reduction and internal fixation (ORIF) for tibia fracture and establish a nomogram prediction model. We retrospectively analysed the clinical data of patients who suffered from tibia fractures and had been surgically treated by ORIF in our institution between August 2015 and October 2020. Perioperative information was obtained through the electronic medical record system, univariate and multivariate analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is especially true in high‐energy calcaneal fractures, where a compromised soft tissue envelope with extensive oedema, fracture blisters, and ecchymosis may be present. 39 , 40 Many surgeons performed surgery after detumescence of the injured foot and suggested that it is critical to avoid soft‐tissue complications. Generally, calcaneal fractures are caused by high‐energy impacts, and the relatively thin coverage of soft tissue on the heel also suffers severe injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true in high‐energy calcaneal fractures, where a compromised soft tissue envelope with extensive oedema, fracture blisters, and ecchymosis may be present. 39 , 40 Many surgeons performed surgery after detumescence of the injured foot and suggested that it is critical to avoid soft‐tissue complications. Generally, calcaneal fractures are caused by high‐energy impacts, and the relatively thin coverage of soft tissue on the heel also suffers severe injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is vitally important for the surgeon to delay surgery until the swelling subsides sufficiently, since wound edge necrosis, skin slough, and postoperative infections can be the consequence of a prematurely performed ORIF. This is especially true in high‐energy calcaneal fractures, where a compromised soft tissue envelope with extensive oedema, fracture blisters, and ecchymosis may be present 39,40 . Many surgeons performed surgery after detumescence of the injured foot and suggested that it is critical to avoid soft‐tissue complications.…”
Section: Discussionmentioning
confidence: 99%